Effect of basic psychological satisfaction needs on resilience in patients with first acute myocardial infarction: the mediating role of family resilience and hope - Ding, Hong; Miao, Liyun; Bai, Yali; Wang, Yan (Frontiers in Psychiatry, 2025)
BackgroundPsychological resilience is key to coping with adversity, stress buffering, and trauma. Acute myocardial infarction (AMI), a major life event, triggers severe psychological stress, especially in first-time patients facing heightened adversity. This diminishes resilience and worsens the prognosis. Evidence links basic psychological need satisfaction to resilience, but the mediating roles of family resilience and hope remain untested. This study aimed to explore the influence of psychological satisfaction needs on the psychological resilience of patients with first-time AMI, and to investigate the chain intermediary role of family resilience and hope in it.MethodsThis cross-sectional study was conducted from June 2023 to June 2025. Patients with first-time AMI and treated at our hospital were enrolled via convenience sampling. Data were collected using Basic Psychological Needs Scales (BPNS), Basic Psychological Needs Scales (BPNS), Family Resilience Assessment Scale (FRAS) and the Herth Hope Index (HHI). Statistical analysis included an independent sample T test, Pearson correlation analysis, linear regression and self-help intermediary analysis.ResultsA total of 179 first-time AMI patients showed mean scores of (62.95 ± 5.71) on the CD-RISC, (110.35 ± 14.00) on the BPNS, (37.28 ± 9.87) on the FRAS, and (24.63 ± 5.93) on the HHI. Significant positive correlations were observed between CD-RISC scores and BPNS, FRAS, and HHI scores (P < 0.05). The total effect of basic psychological needs satisfaction on psychological resilience was significant (β = 0.273, P < 0.001), with a significant direct predictive effect. Basic psychological needs satisfaction positively predicted family resilience (β = 0.489, P < 0.001) and hope (β = 0.262, P < 0.001). Both family resilience (β = 0.211, P < 0.001) and hope (β = 0.273, P < 0.001) demonstrated significant positive effects on psychological resilience. Path analysis confirmed four significant mediation pathways (all 95% CIs excluded zero).ConclusionFamily resilience and hope mediate basic psychological needs and psychological resilience in first-time AMI patients. Clinical care should integrate family-community resources to enhance social support and companionship, aiming to boost patients' resilience and promote prognosis.